Beyond the Bifurcation: There Is More to Cerebrovascular Ultrasound Than Internal Carotid Artery Stenosis!. Issue 3 (September 2016) - Deurdulian, Corinne; Emmanuel, Neelmini; Tchelepi, Hisham; Grant, Edward G.; Malhi, Harshawn
Abstract : Abstract: Carotid ultrasonography (US) is most commonly performed to identify potential areas of flow-limiting stenosis in the internal carotid artery. Identification of stenosis and unstable plaque is important because these entities are leading predictors of stroke, the fourth most common cause of death in the United States. However, US can detect other important but less common vascular pathologies if proper techniques and nuances of these entities are understood. In this article, we discuss the US appearance of abnormalities involving the carotid, vertebral, subclavian, and innominate arteries as well as the key clinical components of each diagnosis. These include congenital variants, dissection, stenosis, and vasculopathy. In addition, correlation of US findings with both magnetic resonance imaging and computed tomography more comprehensively demonstrates the complementary nature of these imaging modalities.